(untitled) (REMUNOM, 2023)
Taxes are a fundamental source of resources for Political Affairs, including municipalities. Among the demands of municipal tax jurisdiction, the Urban Property and Territorial Tax (IPTU) is included, levied on owners or possessors of properties located in the urban area. However, due to certain situations of social or economic vulnerability, exemption hypotheses may be created, which eliminate payment obligations. Furthermore, many Brazilian municipalities have obscure, confusing and flawed legislation that makes it difficult to exercise this benefit. Therefore, the present research has the general objective of critically investigating the problems that surround the hypotheses of exemption from the aforementioned provisions imposed by the municipality of Guaraí, State of Tocantins. Among other pertinent issues, the issue of the procedures adopted for the requirement is discussed, in addition to the lack of clear information about the requirements for granting the benefit. To construct the work in commentary, a methodology of bibliographical research was used, of a qualitative and deductive nature, carried out on doctrines, scientific articles and related legislation, also comparing standards from other municipalities. At the end of the study, it is concluded that the aforementioned authorization is extremely essential for the elderly, people with disabilities and those affected by malignant neoplasia living in Guaraí - TO, however, a change/update of the local standard is essential, with the purpose of facilitate the demand and granting of tax benefits to Guaraiense citizens, in addition to the need for greater publicity to the population. Keywords: Exemption. Urban Property and Territorial Tax. Guaraí-TO.